Kombinasi Spatial dan SnR Scalability dalam Video Streaming - Mira Chandra Kirana (JURNAL INTEGRASI, 2015)
Spatial scalability is a coding method that provides two or more layers in scalable coding process while SNR scalability is a scalability that use more than one layer in scalable coding process. In this method that should be noted are the Base Layer and Enhancement Layer in the resulting graphs. Base layer is obtained by lowering the resolution of the video frame, on the other hand the enhancement layer have to be done the encoding process is quite complex to get video frame quality better.